2022
DOI: 10.1007/s40279-022-01796-8
|View full text |Cite
|
Sign up to set email alerts
|

Mental Performance and Sport: Caffeine and Co-consumed Bioactive Ingredients

Abstract: The plant defence compound caffeine is widely consumed as a performance enhancer in a sporting context, with potential benefits expected in both physiological and psychological terms. However, although caffeine modestly but consistently improves alertness and fatigue, its effects on mental performance are largely restricted to improved attention or concentration. It has no consistent effect within other cognitive domains that are important to sporting performance, including working memory, executive function a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 228 publications
1
11
1
Order By: Relevance
“…Products derived from caffeine-synthesizing plants such as guarana also contain additional bioactive substances which may facilitate mental performance benefits which potentially could exceed those expected from its caffeine content alone [ 41 ]. Flavonoids have been linked to improvement in mental processing speeds [ 26 ]; however, the available published data are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Products derived from caffeine-synthesizing plants such as guarana also contain additional bioactive substances which may facilitate mental performance benefits which potentially could exceed those expected from its caffeine content alone [ 41 ]. Flavonoids have been linked to improvement in mental processing speeds [ 26 ]; however, the available published data are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Ginseng was the second cognitive enhancer, just after caffeine, chosen by the students in our survey (more often by women than men). It was found that single doses of ginseng may improve the accuracy of memory tasks, working memory, or increased speed of attention task performance [ 37 ], and long-term use may positively impact cognitive functions in the future [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with studies reporting that various nutrients (with and without caffeine) may influence cognitive function. Additionally, combining various nootropic nutrients may provide some additive and/or synergistic benefit [7,9,10,14,27,33,47,54,55,57,59,60].…”
Section: Discussionmentioning
confidence: 99%